Question Considered by the Second Emergency Special Session of the General Assembly from 4 to 10 November 1956. A/3521, Eleventh session, Agenda Item 67 - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Péter Mód; United Nations. General Assembly Letter dated February 4, 1957 from the Permanent Representative of Hungary to the United Nations addressed to the Secretary General.